2008
DOI: 10.1161/circulationaha.107.724310
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Integrin Mac-1 Promotes Acute Cardiac Allograft Rejection

Abstract: Background— In allograft rejection, recipient leukocytes and alloantibodies first target donor endothelial cells. Although the leukocyte integrin Mac-1 (α Mβ2 , CD11b/CD18) facilitates cell–cell interactions among leukocytes and interactions between leukocytes and endothelial cells or platelets, its role in allograft survival and vasculopathy is incompletely defined. Methods and Results— T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…Occlusion (GAD) was scored on a scale of 0 to 4 on the extent of luminal occlusion averaged over 10 arteries (0, <10 %; 1, 10–25%; 2, 25–50%; 3, 50–75%; and 4, >75% occlusion of the vascular lumen) as described previously (27). …”
Section: Methodsmentioning
confidence: 99%
“…Occlusion (GAD) was scored on a scale of 0 to 4 on the extent of luminal occlusion averaged over 10 arteries (0, <10 %; 1, 10–25%; 2, 25–50%; 3, 50–75%; and 4, >75% occlusion of the vascular lumen) as described previously (27). …”
Section: Methodsmentioning
confidence: 99%
“…Because neutrophils are able to release numerous mediators, including pro-inflammatory (IL-1α/β; -6; -7; -8; -9; -16), pro-inflammatory/angiogenic (tumor growth factor TGF-α; vascular endothelial growth factor VEGF), and anti-inflammatory mediators (IL-1 receptor antagonist (IL-1RA), TGF-β), they likely play a pivotal yet not well characterized role in the initiation and the development of CAV [28] . Previous studies have demonstrated the potential deleterious role of neutrophils during myocardial reperfusion immediately after CTx in rodents, notably via neutrophil activated αMβ2 integrin complexes (CD11b/CD18) [29,30] . These studies reported that β2 integrin mediated neutrophil infiltration and accumulation in the cardiac allograft tissue was associated with acute rejection in mice.…”
Section: The Pathogenesis Of Cav: An Inflammatory Perspectivementioning
confidence: 99%
“…For complete T cell activation, costimulatory molecules such as CD40, B7 molecules (CD80, CD86), OX40L, ICOS ligand, or PDL1 and PDL2 (programmed cell death ligand) must also ligate host T cell cognate receptors; ␤-integrins can also affect antigen presentation. 19 Recruited and activated T cells then secrete cytokines such as tumor necrosis factor (TNF)-␣ and IFN-␥ that amplify the immune response, increase EC adhesion molecule expression, and lead to further recruitment of macrophages and T lymphocytes. In turn, activated macrophages and lymphocytes express cytokines and growth factors such as plateletderived growth factor, fibroblast growth factor, and transforming growth factor (TGF)-beta (TGF-␤), that promote the recruitment and proliferation of smooth muscle-like cells in the intima and drive extracellular matrix synthesis.…”
Section: Cellular Immunitymentioning
confidence: 99%
“…57 MCP-1 also plays an important contributory role in the pathogenesis of acute organ rejection and GAD. 63 Interestingly, statins attenuate the production of these chemokines in ECs, SMCs, and monocytes, 19,64 and also reduce CCR2 and CCR5 expression by both ECs and macrophages, attenuating GAD. 65 …”
Section: Chemokines and Ecsmentioning
confidence: 99%
See 1 more Smart Citation